Political Emigrants, Prisoners of War and Interned Persons from Russia and Ukraine in Pomerelia (Gdańsk Pomerania) in 1914–1939 - Karpus, Zbigniew (Archiwum Emigracji, 2021)
POLITICAL EMIGRANTS, PRISONERS OF WAR AND INTERNED PERSONS FROM RUSSIA AND UKRAINE IN POMERELIA (GDAŃSK POMERANIA) IN 1914–1939 The article focuses on the Russian and Ukrainian residents of Pomeranian Voivodeship during the inter-war period, particularly those who came first as prisoners of war during World War I and the Polish-Soviet war as well as members of the White Russian forces detained in Poland after the latter conflict ended. Based on archival sources, the text traces the origins of those communities, presenting in detail situation in the camps, differences in assimilation attempts between specific groups of prisoners/migrants after release, as well as the later life of those communities in Pomerelia towns, including the question of religious worship. A separate part is devoted to Ukrainian economic migrants. POLITYCZNI EMIGRANCI, JEŃCY WOJENNI I OSOBY INTERNOWANE Z ROSJI I UKRAINY NA TERENACH POMORZA GDAŃSKIEGO W LATACH 1914–1939 Artykuł koncentruje się na Rosjanach i Ukraińcach, którzy w okresie międzywojennym zamieszkiwali w województwie pomorskim — przede wszystkim na tych, którzy trafili tam jako jeńcy wojenni podczas pierwszej wojny światowej i wojny polsko-bolszewickiej, a także członkach Białej Armii internowanych w Polsce po zakończeniu tego drugiego konfliktu. Na podstawie źródeł archiwalnych tekst analizuje pochodzenie różnych grup osiedleńców, przedstawiając szczegółowo sytuację w obozach a także różnice pomiędzy próbami asymilacji podejmowanymi przez poszczególne grupy byłych jeńców oraz emigrantów. Artykuł opisuje też późniejsze życie tych wspólnot w miastach Pomorza Gdańskiego, w tym kwestię kultu religijnego. Osobna część poświęcona jest emigrantom z Ukrainy, przybywającym na Pomorze głównie w celach zarobkowych.